HUBUNGAN AKTIVITAS FISIK DAN KUALITAS TIDUR DENGAN FUNGSI KOGNITIF MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Alvita Theresia Samosir (2020)
Dense schedules and a lot of academic assignments cause medical students to tend to have poor sleep quality. At this time, students te nd to adopt a sedentary lifestyle. The aims of this study is to determine the relationship between physical activity and sleep quality with cognitive function in students. The cross-sectional study design was used in this study. The subjects of this study were students of the Faculty of Medicine at the Veterans National Development University of Jakarta with mild stress levels. This study uses a simple random sampling technique with a sample size of 91 subjects. Stress scores was measured using the Perceived Stress Scale - 10. Physical activity was assessed using the General Physical Activity Questionnaire (GPAQ). Sleep quality was assessed using the Pitsburgh Sleep Questionnaire Index (PSQI), and cognitive function was evaluated by the Montreal Cognitive Assessment-Indonesia (MoCA-Ina). 68.1% of the subjects were female, most were 19 years old, 56.8% of subjects had moderate activity, 51.6% had poor sleep quality, and 81.3% had a normal cognitive function. The logistic regression test results showed that the sleep quality (p = 0.005, OR = 24.755) and physical activity (p = 0.002, OR = 10.964) have significant correlation with cognitive function